-x+6=y

Simple and best practice solution for -x+6=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+6=y equation:


Simplifying
-1x + 6 = y

Reorder the terms:
6 + -1x = y

Solving
6 + -1x = y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1x = -6 + y

Combine like terms: 6 + -6 = 0
0 + -1x = -6 + y
-1x = -6 + y

Divide each side by '-1'.
x = 6 + -1y

Simplifying
x = 6 + -1y

See similar equations:

| (3x-5)+(7y)=180 | | 6y=-2+3x | | -18w-17=19-20w | | 7x-2=5x-3+2x-1 | | -2*10-3y=-7 | | 17=3x-2(x-5) | | 2p+2p-3=2p+1 | | -20-6k=-k | | 3x-x+2=22 | | 2x^(1/2) | | 27=y/3-13 | | -2*3-3y=-7 | | 4w-22=8w-70 | | 4x+8x^2=9 | | -17g-4=14-8g | | log(45/x)=0.34 | | -96=-6g+2g | | -2*4-3y=-7 | | 2x-24x=-72 | | -8h+10=-9h+18 | | p^2-2p=-1 | | -9f-6f=24 | | -2*2-3y=-7 | | X^5=65 | | 6=v+5v | | 48=5y-12 | | -3-4z=-15 | | 9x-6=12x-3x | | 3(-2x-1)=2x+5 | | 4(1+5g)= | | 4x+12+2x= | | 4(1+5g)=Submit |

Equations solver categories